Relationship between platelet-lymphocyte ratio and tumour infiltrating lymphocyte on metastatic in breast cancer patient - Sejati, Indro Wibowo; Manuaba, Ida Bagus Tjakra Wibawa; Tusta, Putu Anda; Setiawan, Gede Budhi (International Journal of Research in Medical Sciences, 2019)
Background: Platelet-lymphocyte ratio (PLR) is known associated with the prognosis of distant metastatic breast cancer. Tumor-infiltrating lymphocyte (TIL) in breast cancer also associated with the prognosis of distant metastatic breast cancer. In this study, we will examine the relationship between PLR and TIL, in association with the metastatic incidence in breast cancer. Methods: This research is a retrospective, analytic, cross-sectional study. Data was taken from medical records of breast cancer patients at Sanglah general hospital. Samples were taken by nested sampling by selecting all breast cancer patients from the period of January 1st, 2017, to December 31st, 2018, which had complete medical record data, with total sample 211. The PLR and TIL were calculated and analyzed in relation to metastasis incidence of breast cancer. Results: The sample characteristics were sorted by age, education, occupation, the area of origin, menstrual status, breast cancer staging, breast cancer subtype, TIL levels, lymphovascular invasion (LVI) status, metastatic status, and breast cancer grading. The data were analyzed to know the association of PLR, TIL, confounding factors in relation to metastatic incidences. In the sample group with PLR ≥ 156 10µ /µL, there were 22.9% cases of metastases (p = 0.002). The sample group at low TIL had metastatic event 12.5% with (p=0.442). Conclusions: PLR was associated with higher metastasis in breast cancer patients and low TIL had no association with breast cancer metastasis.